2020
DOI: 10.1097/ta.0000000000002969
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the interaction effect between injury regions in multiple injuries: A nationwide cohort study in Japan

Abstract: BACKGROUND There have been no clinical studies to sufficiently reveal the interaction effect generated by combinations of injury regions of multiple injuries. We hypothesized that certain combinations of trauma regions might lead to increased risk of traumatic death and aimed to verify this hypothesis using a nationwide trauma registry in Japan. MATERIALS AND METHODS This was a retrospective study of trauma patients registered in the Japan Trauma Data Bank between 2004 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 38 publications
(11 reference statements)
0
10
0
Order By: Relevance
“…TBI was defined as an injury to the brain due to an external force. Patients with TBI were screened with the Abbreviated Injury Scale (AIS) code [ 6 ]; we excluded cases with AIS ≥ 3 for all other body regions (chest, abdomen, and extremity), as polytrauma associated with TBI is known to increase the risk of mortality [ 7 ]. Furthermore, we excluded patients with a maximum head AIS score of 6 (lethal injury) or 9 (unspecified injury); cardiopulmonary arrest on hospital arrival; a requirement for inter-hospital transport [ 8 , 9 ]; or missing data for variables required for the logistic regression analysis.…”
Section: Methodsmentioning
confidence: 99%
“…TBI was defined as an injury to the brain due to an external force. Patients with TBI were screened with the Abbreviated Injury Scale (AIS) code [ 6 ]; we excluded cases with AIS ≥ 3 for all other body regions (chest, abdomen, and extremity), as polytrauma associated with TBI is known to increase the risk of mortality [ 7 ]. Furthermore, we excluded patients with a maximum head AIS score of 6 (lethal injury) or 9 (unspecified injury); cardiopulmonary arrest on hospital arrival; a requirement for inter-hospital transport [ 8 , 9 ]; or missing data for variables required for the logistic regression analysis.…”
Section: Methodsmentioning
confidence: 99%
“…We assessed trends in elderly patients with TBI. Furthermore, we considered isolated TBI and multiple trauma (a combination of trauma in the head and other regions) separately as trauma in multiple regions has been associated with a greater risk of traumatic death compared with isolated TBI [11]. Since the increasing number of elderly patients affects total mortality, we hypothesized that the trend of TBI-related mortality would worsen as society ages.…”
Section: Introductionmentioning
confidence: 99%
“…High-mortality groups exhibited a high degree of impaired consciousness and were further divided into a severe traumatic brain injury group and a polytrauma group according to reasonable clinical parameters. In trauma epidemiology, associations between combinations of injured regions and trauma-related mortality have been examined using a logistic model that included interaction effects and demonstrated significant interactions with mortality in head–chest and chest–pelvic/extremities injuries [ 2 ]. In the present study, clustering analysis revealed that injuries to the chest, pelvis, and extremities in the polytrauma group were associated with a high mortality rate.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, correctly determining the effects of therapeutic interventions remains intractable. Studies using large-scale registry data have attempted to validate interaction effects to identify groups with fatal polytrauma and reported that specific combinations of injuries significantly affect patient outcomes [ 2 ]. Thus, in analyses that consider the effects of complex, nonlinear interactions may reveal the pathological conditions that interact with multiple factors.…”
Section: Introductionmentioning
confidence: 99%